2016
DOI: 10.1016/j.jallcom.2016.05.108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Sn content on mechanical, magnetization and shape memory behavior in NiMnSn alloys

Abstract: The effects of the composition alteration on the magnetization and shape memory behavior of Ni50Mn40-xSn10+x (x=0, 1, 2, 3) alloys were systematically investigated by thermal, magnetic and mechanical experiments. Phase transformation from ferromagnetic austenite to weakly magnetic martensite was observed during thermal cycling under magnetic field and transformation temperatures were decreased with increasing Sn (or decreasing Mn). Moreover, the saturation magnetization of martensite increased with Sn content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…It was clearly seen that NiMnSn-HA and its components have the hysteresis loops with hard ferromagnetic characteristic, which is related to high coercivity. These results, except for those of its Mn2 components, are a quantitatively good accordance with the theoretical report of Ni50Mn36Sn14 Heusler alloy by Duran [35] and with the experimental reports of Ni50Mn36Sn14 alloy by Li et al [66], Mn2Ni1.6Sn0.4 melt-spun ribbons by Singh et al [67], Ni50Mn36Sn14-xSix alloys by Raji et al [29], Ni50Mn40-xSn10+x alloys by Aydogdu et al [18]. In Fig.…”
Section: The Numerical Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It was clearly seen that NiMnSn-HA and its components have the hysteresis loops with hard ferromagnetic characteristic, which is related to high coercivity. These results, except for those of its Mn2 components, are a quantitatively good accordance with the theoretical report of Ni50Mn36Sn14 Heusler alloy by Duran [35] and with the experimental reports of Ni50Mn36Sn14 alloy by Li et al [66], Mn2Ni1.6Sn0.4 melt-spun ribbons by Singh et al [67], Ni50Mn36Sn14-xSix alloys by Raji et al [29], Ni50Mn40-xSn10+x alloys by Aydogdu et al [18]. In Fig.…”
Section: The Numerical Resultssupporting
confidence: 90%
“…In that case, it can be suggested that its Mn2 component displays a weak first order phase transition at a temperature value between 1.00 to 1.25 according to the hysteresis behaviors. These ferromagnetic hysteresis behaviors are in a good accordance with the theoretical report of Ni50Mn36Sn14 Heusler alloy by Duran [35] and with the experimental reports of Ni50Mn36Sn14 alloy by Li et al [66], Mn2Ni1.6Sn0.4 melt-spun ribbons by Singh et al [67], Ni50Mn36Sn14-xSix alloys by Raji et al [29], Ni50Mn40-xSn10+x alloys by Aydogdu et al [18]. The HC values of the HA and its components are zero and the hysteresis loops of NiMnSn-HA and its components lose at T>TC as it is seen in Fig.…”
Section: The Numerical Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Sample obtained after ice water quenching was prepared for microstructural study after mechanical grinding with abrasive papers of different grades followed by polishing on velvet cloth with diamond paste. In order to reveal the microstructure of the alloy, polished sample was etched with a solution of 10 ml HCl, 2.5gm FeCl 3 ‐H 2 O and 48 ml methanol . Microstructural analysis of the sample was performed using Optical Microscope (Zeiss AX10) and Scanning Electron Microscope (SEM: Nova Nano FE‐SEM 450 (FEI); chemical composition was determined by Energy Dispersive X‐ray Spectroscopy (EDS: Oxford Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of Heusler alloys traces back to 1903, when Fritz Heusler observed ferromagnetic behavior on Cu 2 MnAl, an intermetallic formed entirely by nonferromagnetic elements. These are magnetic materials with important technological applications due to shape memory behavior, , magnetocaloric effect, , magnetoresistance, , half-metallicity, and thermoelectrical properties …”
Section: Introductionmentioning
confidence: 99%